2021
DOI: 10.1093/molbev/msab238
|View full text |Cite
|
Sign up to set email alerts
|

Papua New Guinean Genomes Reveal the Complex Settlement of North Sahul

Abstract: The settlement of Sahul, the lost continent of Oceania, remains one of the most ancient and debated human migrations. Modern New Guineans inherited a unique genetic diversity tracing back 50,000 years, and yet there is currently no model reconstructing their past population dynamics. We generated 58 new whole genome sequences from Papua New Guinea, filling geographical gaps in previous sampling, specifically to address alternative scenarios of the initial migration to Sahul and the settlement of New Guinea. He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
47
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(55 citation statements)
references
References 67 publications
7
47
1
Order By: Relevance
“…8A), and Austronesian segments are widely shared among the PNG lowland and island groups but not with the highlands (Fig. 8B), in keeping with previous observations of a lack of Austronesianassociated ancestry in the PNG highlands (27,28,32,34). However, sharing of Papuan segments is strictly either among mainland PNG and Massim groups, or among groups from the Bismarcks and Solomons; there is no sharing of Papuan-related IBD segments between any mainland PNG or Massim group and any group from the Bismarcks or Solomons (Fig.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…8A), and Austronesian segments are widely shared among the PNG lowland and island groups but not with the highlands (Fig. 8B), in keeping with previous observations of a lack of Austronesianassociated ancestry in the PNG highlands (27,28,32,34). However, sharing of Papuan segments is strictly either among mainland PNG and Massim groups, or among groups from the Bismarcks and Solomons; there is no sharing of Papuan-related IBD segments between any mainland PNG or Massim group and any group from the Bismarcks or Solomons (Fig.…”
Section: Discussionsupporting
confidence: 91%
“…Previous studies of genome-wide data have shown a major distinction between Papuan ancestries in the PNG Highlands vs. Bougainville (32), and in the western vs. eastern regions of the PNG Highlands (27,28). We find support for both of these distinctions, as well as for a novel Papuan-related ancestry on Rossel (Figs.…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations